"Chopcula" i jej tajemniczy świat — o autobiograficzności w poezji Małgorzaty Lebdy - Bukowska, Weronika (Zagadnienia Rodzajów Literackich, 2023)
The aim of this article is to present the autobiographical character in the poetry of Małgorzata Lebda, whose work is filled with personal experiences and memories, especially those of the poet’s childhood and youth spent in her family village — Żeleźnikowa Wielka. The issue is based on the example of her debut volume — Tropy (2009) and the poetic triptych — Sprawy ziemi (2020), which consists of three earlier poetry volumes published by Lebda: Border of the Forest (2013), Matecznik (2016) and Dreams of the Uckermärkers (2019). Full of autobiographical experiences, Lebda’s poetry turns out to be at the same time a site for playing with memory, with memories and for working through difficult, traumatic experiences. The article also contains an analysis of the construction of the lyrical subject — chopcula — inextricably linked to the space of Lebda’s autobiographical place — Żeleźnikowa Wielka. The poet’s hometown also turns out to be a fairy-tale land of the girl’s childhood and youth, but at the same time it has been marked by trauma, which the author tries to work through with the help of memory in her poems. The article also reflects on the poet’s play with memory and her use of memories in her works, as well as on the ‘matters of the forest’ close to her, into which the lyrical subject is introduced by her father.